2013
DOI: 10.1016/j.aap.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile Internet use on college student pedestrian injury risk

Abstract: Background College-age individuals have the highest incidence of pedestrian injuries of any age cohort. One factor that might contribute to elevated pedestrian injuries among this age group is injuries incurred while crossing streets distracted by mobile devices. Objectives Examine whether young adult pedestrian safety is compromised while crossing a virtual pedestrian street while distracted using the internet on a mobile “smartphone.” Method A within-subjects design was implemented with 92 young adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 20 publications
5
94
0
1
Order By: Relevance
“…Texting involves reading and typing, which is more cognitively demanding than talking [11]. Similar to texting, replying to emails and gaming also require cognitive attention that may take a serious toll on safe pedestrian behavior [13,14].…”
Section: Research Studies On Distracted Pedestriansmentioning
confidence: 99%
See 1 more Smart Citation
“…Texting involves reading and typing, which is more cognitively demanding than talking [11]. Similar to texting, replying to emails and gaming also require cognitive attention that may take a serious toll on safe pedestrian behavior [13,14].…”
Section: Research Studies On Distracted Pedestriansmentioning
confidence: 99%
“…The distracted pedestrians tended to walk slower, were more likely miss the crossing opportunities, and were more likely to be hit or almost hit because they look at their mobile phones instead of around the street environment. Trial duration [4,5,11,13], success rate [4], time-out rate [4,11], missed opportunities [5,11,13], attention to traffic [5,11,13], and hits/close calls [4,5,11,13] were the parameters used in quantifying the performance of pedestrians when crossing the street.…”
Section: Success Rate Of the Primary Taskmentioning
confidence: 99%
“…Due to distractions, it is shown that it can significantly affect crossing speed, increase conflict, less attention to environment and many more errors which possibly end up with accident [9][10][11][12]. Pedestrian's distraction while crossing is a major issue in developed countries and those countries proactively take this issue and come out with various intervention that suit to their cultures and laws.…”
Section: Pedestrian Distractionmentioning
confidence: 99%
“…The activities were all equally distracting-pairwise comparisons found no differences among the three distraction conditions in that a naturalistic cell phone conversation resulted in pedestrian behaviors as risky as the behaviors exhibited while engaging in the spatial-and arithmeticfocused conversations. Byington and Schwebel (2013) recorded the behavior of 92 participants crossing a street in a virtual environment. They recruited participants from an introductory psychology class at the University of Alabama at Birmingham.…”
Section: Simulation Observationmentioning
confidence: 99%